Teachers' readiness in teaching and learning in science subject through I-Think mind maps in Jempol District, Negeri Sembilan - Arimuthu, Vimala; Kamarudin, Nurzatulshima; Abdul Manaf, Umi Kalthom (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
The development of thinking skills in school has been revised and improved due to produce individual with intellect as stated in National Education Philosophy. The Malaysian Education has big gone through a transformation in order to enhance thinking skills among students. I-think programme is one of the ways to stimulate thinking skills and it is a teaching tools that help teachers to excite students’ thinking, learning progress, and boost metacognitive behaviour during the teaching and learning processes. This programme is one of efforts to create a new culture of thinking in schools. This case study will be conducted in Jempol District among Tamil Schools which will involves 40 trained Science teachers to identify the teachers’ readiness in teaching and learning in Science subject through i-Think mind maps. This study uses quantitative methods and data will be obtained through questionnaire. The findings will helps teachers to assess their level of readiness in I-Think mind map, the level of understanding the concept of I-Think mind map and the level of readiness in utilization skills in I-Think mind map. Through this, teachers will be able to complete themselves with I-Think knowledge to ensure successful implementation. The successful implementation will produce students with critical, creative, innovative and analytical skills. Therefore, teachers play a vital role in order to make it a success.